(untitled) (Bangladesh Journal of Agriculture, 2025)
The sunflower (Helianthus annuus L.), a vital oilseed crop that significantly reduces production globally, is seriously threatened by collar rot, a disease caused by the soil-borne fungus Sclerotium rolfsii reductions. This research sought to assess the effectiveness of various control methods against S. rolfsii in laboratory conditions, including nine fungicides, nine plant extracts, and five organic amendments. This study assessed the efficacy of various medicinal plant extracts at different concentrations (5%, 10%, 15%, and 20%) in inhibiting the in vitro mycelial growth of S. rolfsii. Among the plant extracts tested, garlic demonstrated the most potent antifungal properties, completely suppressing mycelial growth at 10%, 15%, and 20% concentrations. The results indicate that garlic clove extract (98.18-100%) is the most effective at inhibiting S. rolfsii growth, with henna (65.92-92.46%) and black cumin extracts (64.80-85.88%) also demonstrating strong efficacy. The fungicide Carboxin and Thiram (Provax 200) were found most effective, achieving total inhibition, followed by Azoxystrobin and Difenoconazole (Amister Top) (91%) and Difenoconazole (Score) (90%). In the case of the extracts of organic amendment material, poultry refuse exhibited the highest inhibition, completely inhibiting the mycelial growth at 20% and 30% concentrations. Among the organic amendments, poultry refuse (94.40-100%), vermicompost (17.55-67.32%), and mustard oilcake (14.88-64.10%), showed strong potential for reducing S. rolfsii mycelial growth. The findings of the study suggest that Carboxin and Thiram, poultry refuse, and garlic extract could be effective in managing sunflower collar rot disease. Bangladesh J. Agri. 2024, 49(2): 1-15